Measuring the prevalence and impact of poor menstrual hygiene management: a quantitative survey of schoolgirls in rural Uganda. Issue 12 (30th December 2016) - Hennegan, Julie; Dolan, Catherine; Wu, Maryalice; Scott, Linda; Montgomery, Paul
Abstract : Objectives: The primary objective was to describe Ugandan schoolgirls' menstrual hygiene management (MHM) practices and estimate the prevalence of inadequate MHM. Second, to assess the relative contribution of aspects of MHM to health, education and psychosocial outcomes. Design: Secondary analysis of survey data collected as part of the final follow-up from a controlled trial of reusable sanitary pad and puberty education provision was used to provide a cross-sectional description of girls' MHM practices and assess relationships with outcomes. Setting: Rural primary schools in the Kamuli district, Uganda. Participants: Participants were 205 menstruating schoolgirls (10–19 years) from the eight study sites. Primary and secondary outcome measures: The prevalence of adequate MHM, consistent with the concept definition, was estimated using dimensions of absorbent used, frequency of absorbent change, washing and drying procedures and privacy. Self-reported health, education (school attendance and engagement) and psychosocial (shame, insecurity, embarrassment) outcomes hypothesised to result from poor MHM were assessed as primary outcomes. Outcomes were measured through English surveys loaded on iPads and administered verbally in the local language. Results: 90.5% (95% CI 85.6% to 93.9%) of girls failed to meet available criteria for adequate MHM, with no significant difference between those using reusable sanitary pads (88.9%, 95% CI 79.0% to 94.4%) and those using existing methods, predominantly cloth (91.5%, 95% CI 85.1% to 95.3%; χ 2 (1)=0.12, p=0.729). Aspects of MHM predicted some consequences including shame, not standing in class to answer questions and concerns about odour. Conclusions: This study was the first to assess the prevalence of MHM consistent with the concept definition. Results suggest that when all aspects of menstrual hygiene are considered together, the prevalence is much higher than has previously been reported based on absorbents alone. The work demonstrates an urgent need for improved assessment and reporting of MHM, and for primary research testing the links between menstrual management and health, education and psychosocial consequences.